Dextran sulfate-coated superparamagnetic iron oxide nanoparticles as a contrast agent for atherosclerosis imaging - You, Dong Gil; Sarayanakumar, Gurusamy; Son, Soyoung; Han, Hwa Seung; Heo, Roun; Kim, Kwangmeyung; Kwon, Ick Chan; Lee, Jun Young; Park, Jae Hyung (ELSEVIER SCI LTD, 2014)
The hallmark of atherosclerosis in its early pathogenic process is the overexpression of class A scavenger receptors (SR-A) by activated macrophages. In this study, dextran sulfate-coated superparamagnetic iron oxide nanoparticles (DS-SPIONs), as a magnetic resonance (MR) imaging contrast agent of atherosclerosis, was prepared via the facile co-precipitation method using a versatile double-hydrophilic block copolymer comprising of a DS segment (ligand for SR-A) and a poly(glyclerol methacrylate) segment (SPIONs surface-anchoring unit). The physicochemical properties of the DS-SPIONs were investigated using various instruments. DS-SPIONs exhibited high aqueous stability compared to dextran-coated SPIONs (Dex-SPIONs), which were used as controls. The cellular uptake behaviors of DS-SPIONs and Dex-SPIONs were evaluated using Prussian blue assay. Interestingly, the DS-SPIONs were effectively taken up by activated macrophages compared to Dex-SPION5. However, the cellular uptake of DS-SPIONs by activated macrophages was remarkably reduced in the presence of free DS. These results suggest that activated macrophages internalize DS-SPIONs via receptor (SR-A)-mediated endocytosis. T-2-weighted MR imaging of the cells demonstrated that activated macrophages treated with DS-SPIONs showed a significantly lower signal intensity compared to those treated with Dex-SPIONs. Overall, these results suggest that DS-SPIONs may be utilized as a potential contrast agent for atherosclerosis MR imaging. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: IN-VIVO DETECTION; MAGNETIC-RESONANCE; SCAVENGER RECEPTOR; CLASS-A; MACROPHAGES; PARTICLES; CANCER; PLAQUE; INFLAMMATION; MECHANISMS